"W waszych rękach teraz los wasz" - elementy perswazji w spektaklu W imię Jakuba S. Moniki Strzępki i Pawła Demirskiego - Gołos-Dąbrowska, Katarzyna (Załącznik Kulturoznawczy, 2018)
The article is an attempt to define how the mechanisms of persuasion function in Monika Strzępka’s and Paweł Demirski’s play W imię Jakuba S. The director and the playwright are representatives of engaged theatre. In their work, they oppose neoliberalism and, above all, the unfulfillable promises it makes. As a result, despite democracy, the phenomenon of serfdom appears again – this time in a form of bank credit. The creators of the performance, apart from expressing views, want to stimulate the viewer to take a critical look at capitalism. In order to do so, they use both verbal and non-verbal means of persuasion.